2008
DOI: 10.1177/1070496507312575
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Waste Generation and Socioeconomic Drivers

Abstract: Using data sets from Italian provinces that include rich northern and poorer southern regions, this article examines to what extent income and municipal waste generation are linked and at what level of income they become delinked. The analysis shows that the turning point occurs at very high levels of value added per capita (in the range of 22,586 to 31,611), exemplified by a very limited number of wealthy (northern) Italian provinces. The authors also find that some recently adopted waste policy and waste man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(43 citation statements)
references
References 25 publications
3
37
0
3
Order By: Relevance
“…Mazzanti et al (2008) find some WKC evidence and signs that waste management instruments do have an effect on reducing waste generation in Italy, where trends are affected by economic, policy and structural geographical differences. 5 There are also some studies on specific evaluations of the Landfill Directive-the main driver of regulatory actions in the EU, and the UK landfill tax-introduced in 1996 and one of the few cases of a real environmental tax based on evaluation of the marginal external costs.…”
Section: Delinking Analysis and Wkc: Empirical Evidencementioning
confidence: 95%
“…Mazzanti et al (2008) find some WKC evidence and signs that waste management instruments do have an effect on reducing waste generation in Italy, where trends are affected by economic, policy and structural geographical differences. 5 There are also some studies on specific evaluations of the Landfill Directive-the main driver of regulatory actions in the EU, and the UK landfill tax-introduced in 1996 and one of the few cases of a real environmental tax based on evaluation of the marginal external costs.…”
Section: Delinking Analysis and Wkc: Empirical Evidencementioning
confidence: 95%
“…Some of the existing literature has indicated that waste production has a strong positive correlation with economic T A B L E 3 LHVs of biomass feedstocks and energy conversion coefficients development and population density at a 0.1 km resolution at the municipal and provincial levels (Mazzanti, Montini, & Zoboli, 2008;Shu, Wang, & Sun, 2012;Xu, Yan, & Cui, 2013). In this research, the statistical downscaling method is used to spatialize waste based on the dataset of GDP, land-use, and the population at 1 km resolution (Li, Zhang, & Yang, 2014;Wilby et al, 1998Wilby et al, , 2004Zhu, Yang, & Zhao, 2011).…”
Section: Estimation and Statistical Downscaling Of Wastementioning
confidence: 99%
“…She finds for OECD that municipal solid waste (MSW) increases monotonically with income and that urbanisation exerts an even stronger effect on waste generation, while the time-invariant policy index is not significant. At country level, Mazzanti et al (2008) analyze waste generation dynamics, showing that only the richest provinces are close to a turning point in the waste income relationship, with strong north south gaps and an effective role of waste management systems like tariffs, which are nevertheless associated to endogeneity with respect to income. Mazzanti and Zoboli (2009), based on panel data for a group of European countries, finds also neither absolute nor relative delinking, for municipal or packaging waste for 1995-2000 and 1997-2000 respectively.…”
mentioning
confidence: 99%